HUBUNGAN KEBIASAAN JAJAN DENGAN STATUS GIZI SISWA SD NEGERI 55 KOTA BANDA ACEH - Julinar Julinar; Silvia Yasmin Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Foods consumed by children will greatly affect the growth of the child itself, if the food is less meet the nutrients needed by the body then the child will megalami growth disorders. The purpose of this research is to know the relationship of snack habits with nutritional status of the students of SD Negeri 55 Banda Aceh. This research was conducted on March 24, 2018 until April 04, 2018. Descriptive explorative research design with a total sample of 67 respondents. The result of univariate research shows that 55,2% respondents with bad habit of snacking, 59,7% of respondents with knowledge of bad snack habit, 58,2% of respondents with negative eating habit, 56,7% respondent with habitual behavior of poor snack, as many as 56,7% of respondents with malnutrition status. Bivariate shows that there is relationship of habit of snack with nutrient status of SD Negeri 55 Kota Banda Aceh Year student in 2018. with p value = 0,039. It is recommended for schools to provide information to students on how to choose healthy snacks and provide rules for merchants not to sell in front of school at break time.Keywords: Habit of Pocket, Knowledge, Attitude, Behavior, Nutritional Status